2015
DOI: 10.1002/mabi.201500276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immobilized Thiolated Glycosaminoglycans on Fibronectin Adsorption and Behavior of Fibroblasts

Abstract: Glycosaminoglycans (GAGs) chondroitin sulfate, heparin, hyaluronan, and sulfated hyaluronan are lower and higher thiolated to enable a one-step covalent modification of gold or vinyl-terminated surfaces. Measurements of water contact angle and zeta potentials reveal that sulfated GAG-modified surfaces are more wettable and possess a negative surface potential. Additionally, higher thiolated GAGs (tGAGs) exhibit increased wettability and higher surface roughness. Fibronectin (FN) adsorption increases with sulfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 67 publications
(108 reference statements)
2
16
0
Order By: Relevance
“…Finally, the most hydrophilic BCS/AVI system has lowest WCA and negative surface potentials at pH 7.4, which normally are not supportive for cell adhesion. However, the presence of BCS in this system may allow for the binding of adhesive proteins with heparin‐binding domains like fibronectin (FN) and vitronectin (VN) from serum, which may promote cell adhesion as demonstrated for other functionalized chondroitin sulfates in previous studies …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Finally, the most hydrophilic BCS/AVI system has lowest WCA and negative surface potentials at pH 7.4, which normally are not supportive for cell adhesion. However, the presence of BCS in this system may allow for the binding of adhesive proteins with heparin‐binding domains like fibronectin (FN) and vitronectin (VN) from serum, which may promote cell adhesion as demonstrated for other functionalized chondroitin sulfates in previous studies …”
Section: Resultsmentioning
confidence: 95%
“…Although the synthetic PSS/PAH system is not suitable for a clinical application as it was used here as a kind of reference system because of its known cytocompatibility . The other two systems were included due to the known osteogenic activity of fibrinogen and the inherent bioactivity of chondroitin sulfate toward proteins with heparin‐binding domains . Physical studies showed that the PSS/PAH multilayer system was well separated with intermediate wetting properties, opposing sign of charge of terminal PSS and PAH layers, which was also the case for BCS/FBG multilayer system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance the adsorption of macromolecular cell‐binding ligands like ECM proteins (collagen, laminin, etc.) or glycosaminoglycan (i.e., heparin or hyaluronic acid) is used to improve cell adhesion and proliferation on biomaterials . The multivalent physical interaction of these ligands is relative unspecific and in most cases mainly mediated by electrostatic attraction between contrary charged functional groups .…”
Section: Introductionmentioning
confidence: 99%
“…or glycosaminoglycan (i.e., heparin or hyaluronic acid) is used to improve cell adhesion and proliferation on biomaterials. [14][15][16][17] The multivalent physical interaction of these ligands is relative unspecific and in most cases mainly mediated by electrostatic attraction between contrary charged functional groups. [18][19][20] However passive adsorbed coatings can be unstable under physiological conditions by displacement and/or superposition of unspecific absorbed plasma proteins.…”
Section: Introductionmentioning
confidence: 99%